Lack of phosphatidylinositol 3-kinase VPS34 in regulatory T cells leads to a fatal lymphoproliferative disorder without affecting their development - Courreges, Christina J. F.; Davenport, Elizabeth C. M.; Bilanges, Benoit; Rebollo-Gomez, Elena; Hukelmann, Jens; Schoenfelder, Priya; Edgar, James R.; Sansom, David; Scudamore, Cheryl L.; Roychoudhuri, Rahul; Garden, Oliver A.; Vanhaesebroeck, Bart; et al. (Frontiers in Immunology, 2024)
Regulatory T (Treg) cells are essential for the maintenance of immunological tolerance, yet the molecular components required for their maintenance and effector functions remain incompletely defined. Inactivation of VPS34 in Treg cells led to an early, lethal phenotype, with massive effector T cell activation and inflammation, like mice lacking Treg cells completely. However, VPS34-deficient Treg cells developed normally, populated the peripheral lymphoid organs and effectively supressed conventional T cells in vitro. Our data suggest that VPS34 is required for the maintaining normal numbers of mature Treg. Functionally, we observed that lack of VPS34 activity impairs cargo processing upon transendocytosis, that defective autophagy may contribute to, but is not sufficient to explain this lethal phenotype, and that loss of VPS34 activity induces a state of heightened metabolic activity that may interfere with metabolic networks required for maintenance or suppressive functions of Treg cells.